Tax knowledge and tax compliance among taxpayers in Malaysia/ Fatimah Alwi and Noraizah Abu Bakar - Alwi, Fatimah; Abu Bakar, Noraizah (Bahagian Penyelidikan Jaringan Industri dan Alumni, 2012)
The tax system in Malaysia has been revamped in order to improve its efficiency. One of the major changes was the implementation of Self Assessment System (SAS) in the basis year (BY) 2000. The most prominent feature of SAS is that taxpayers now are required to compute their own tax liabilities. As a result, the Inland Revenue Board (IRB) is now able to perform tax audits vigorously. Nero et al (2010) and Mohd and Ahmad (2011) suggested a similar conclusion that tax knowledge is vital for tax compliance. However, Lo and Ho (2005) and Madi et al (2010) reported that individual taxpayers in Malaysia had considerably low tax knowledge. Therefore, this qualitative study is performed to explore tax knowledge and tax compliance among the self-employed in Malaysia. Data regarding samples’ tax knowledge and tax compliance in relation to individual income will be collected via interviews. The significant of the study is to provide extended knowledge and to increase tax compliance among self-employed taxpayers.